Buried Barrett's Esophagus with High-Grade Dysplasia after Radiofrequency Ablation - Joana Castela; Miguel Serrano; Susana Mão de Ferro; Daniela Vinha Pereira; Paula Chaves; António Dias Pereira (Korean Society of Gastrointestinal Endoscopy, 2019)
Radiofrequency ablation therapy is an effective endoscopic option for the eradication of Barrett's esophagus that appears to reduce the risk of esophageal cancer. A concern associated with this technique is the development of subsquamous/buried intestinal metaplasia, whose clinical relevance and malignant potential have not yet been fully elucidated. Fewer than 20 cases of subsquamous neoplasia after the successful radiofrequency ablation of Barrett's esophagus have been reported to date. Here, we describe a new case of subsquamous neoplasia (high-grade dysplasia) following radiofrequency ablation that was managed with endoscopic resection. Our experience suggests that a meticulous endoscopic inspection prior to and after radiofrequency ablation is fundamental to reduce the risk of buried neoplasia development.